Enrichment of biomethane production from paper industry biosolid using ozonation combined with hydrolytic enzymes. (1st November 2020) - Sethupathy, A.; Arun, C.; Sivashanmugam, P.; Kumar, R. Ranjith
Graphical abstract: Highlights: OZNCE method has effectively improved the disintegration of PPMW biosolid. OZNCE method was achieved 31% of lysis rate at 15 min of pretreatment time. Higher methane production of 324 L/kg VS was noted for OZNCE method. Combinative method was achieved a net energy of 168 kWh/ton of biosolid. Abstract: In this study, ozonation (OZN) combined consortium of hydrolytic enzymes (CE) method was studied for augmenting anaerobic biodegradability (ABD) of pulp and paper industry waste (PPMW) biosolid. Initially, OZN method was performed by varying ozone dosage and pretreatment time. A higher lysis rate and suspended solids (SS) reduction were noticed respectively to be 20% and 15% at an optimized ozone dosage (0.04 g/g TS) and pretreatment time (24 min). For further enhancing PPMW biosolid disintegration, OZNCE method was proceeded with respect to CE dosage and pretreatment time at an optimized ozone dosage (0.04 g/g TS). At 10% v/v CE dosage and 15 min pretreatment time, maximum of lysis rate (31%) and SS reduction (23.5%) were achieved. The pretreated biosolids were subjected to ABD assay in which OZNCE method obtained higher methane gas production potential of 324 L/kg VS. Also, cost analysis was done, which revealed that OZNCE method obtained a net profit of 15 $ per ton of PPMW biosolid.